KETAHANAN PEREMPUAN KORBAN KDRT DENGAN PENDEKATAN SOCIO-LEGAL DALAM PERSPEKTIF HUKUM ISLAM : STUDI KUALITATIF DI NAGARI TALANG - Fhuja Putri Okta minal; Yusrial; Ade Daharis (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The purpose of this study is to thoroughly describe the coping mechanisms used by female victims of domestic violence in Nagari Talang and to examine this phenomenon by reviewing Islamic law. The descriptive qualitative methodology in this study uses in-depth interviews and observations of victims of domestic violence in communities that uphold the values of Adat Basandi Syarak and Syarak Basandi Kitabullah. According to the results of the study, despite the imbalance of power, women in Nagari Talang demonstrate mental and spiritual resilience, which is based on the ideas of patience and responsibility for the future of their children. From an Islamic legal perspective, it was found that while the victims prioritized the ideal of ishlah (peace), their acceptance of ongoing violence contradicted the principles of Maqashid Syariah, particularly the protection of life (hifdzun nafs) and honor (hifdzun 'irdh). Islam allows women to demand their rights to security and justice through the mechanisms of nusyuz or khulu' from their husbands if the welfare of the household is no longer achieved, so this steadfastness should not be misinterpreted as acceptance of injustice. The findings of this study show that, in order to break the cycle of domestic violence without neglecting religious principles, an emancipatory religious understanding and support are needed.